Biochar Improves Plant Growth and Reduces Nutrient Leaching in Red Clay Loam and Sandy Loam - Pudasaini, Kalpana; Ashwath, Nanjappa; Walsh, Kerry; Bhattarai, Thakur (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
A factorial pot experiment was conducted using two types of soils (sandy loam and red clay loam) that are commonly used for commercial vegetable production in Bundaberg, region of Central Queensl and Australia. The soils were amended with 0, 25, 50 and 75 t/ha of green waste biochar and minimum doses of N, P and K (30 kg/ha, 30 kg/ha and 40 kg/ha respectively). After two weeks of plant establishment, the pots were leached with 1.5 litres of deionised water at week intervals, and cation concentrations of the leachate were determined. In 25 t/ha biochar treatment, there was a significant (P<0.05) reduction in K and Ca leaching by 40% and 26% respectively from sandy loam, and of Ca by 23% from the red clay loam. Soil water holding capacity and soil organic carbon were also increased in both biochar treated soils. After 12 weeks of growth, shoot weight was signifi cantly (P<0.05) higher in 25 t/ha biochar-treated sandy loam and red clay loam (32% and 31% respectively). These results clearly demonstrated that a higher yield of capsicum can be achieved from green waste biochar application in sandy loam and red clay loam at 25 t/ha biochar. DOI: http://dx.doi.org/10.3126/hn.v11i1.7221 Hydro Nepal Special Issue: Conference Proceedings 2012 pp.86-90